Pengaruh saham syariah, reksa dana syariah dan investasi asing terhadap pertumbuhan ekonomi di Indonesia tahun 2011-2020 - Nurjanah (Jurnal Investasi Islam, 2022)
This study aims to determine the effect of Islamic stocks, Islamic mutual funds and foreign investment on economic growth i n Indonesia from 2011-2020. This study uses quantitative methods with multiple linear regression analysis. The results show that Islamic stocks have a negative and significant effect on economic growth with a significant value of 0.04 and a regression coefficient of -3.676. Islamic mutual funds have a positive and significant effect on economic growth in Indonesia with a significant value of 0.01 and a regression coefficient of 0.922. Foreign investment has a positive and significant impact on Indonesia economic growth with a significant value of 0.04 and a regression coefficient of 1.794.